Menciptakan Lapangan Kerja Bagi Fresh Graduate Melalui Program Workshop Dan Seminar Move On Entrepreneur - Alfatih S. Manggabarani; Nunuk Triwahyuningtyas (Institut Ilmu Sosial dan Manajemen Stiami, 2019)
Through this service, we hope to empower the optimal candidates, so that new graduates can take part in Smart Jurus Seminars and Workshops Gaining Business Wealth.